Computational investigation into the effect of pitch ratio on B-series propeller performance (Journal of Naval Architecture and Marine Engineering, 2023)
This study presents Computational Fluid Dynamics (CFD) simulation to predict the thrust coefficient (KT), torque coefficient (KQ) and efficiency (η) in open-water conditions. The effect of various pitch ratio (P/D) and blade number (Z) for the type of B-series have been appropriately taken into account in the computational simulation.  In general, the results revealed that the higher value of advance ratio leads to decrease the values of KT and KQ coefficients. In addition to the propeller’s efficiency, it proportionally increases with respect to the advance number (J); then it adequately decreases at J > 0.8. It should be noted here that the subsequent increase of propeller pitch ratio within the range of 0.6 ≤ P/D ≤1.3 is proportional to the values of KT, KQ and η. This can be explained by the fact that the increase of pitch ratio resulted in the increase of the scalar torque and static pressure. Meanwhile, the propeller with P/D = 1.3 produces the highest efficiency by 81.2% at J=1.15. Furthermore, the propeller with five blade number (Z=5) has the lowest propeller efficiency, which occurred due to increase of the projected blade area. Merely, the current computational result is very useful for acquiring a fundamental understanding of the propeller quantities, especially in open-water conditions.